The role of doping in spin reorientation and terahertz spin waves in SmDyFeO3 single crystals. (12th December 2017) - Liu, Xiumei; Jin, Zuanming; Zhang, Shunnong; Zhang, Kailin; Zhao, Weiyao; Xu, Kai; Lin, Xian; Cheng, Zhenxiang; Cao, Shixun; Ma, Guohong
Abstract: In this work, by using terahertz time-domain spectroscopy (THz-TDS), we investigate the temperature range of the SRT, and the resonant frequency and relaxation time of the THz spin waves in Sm x Dy1− x FeO3 single crystal. We show that the resonant frequency of the FM mode (measured at 40 K) increases linearly with the Sm dopant concentration within the range from x   =  0.5 to 0.7. The temperature- and dopant-induced changes of the magnetic anisotropy of Fe 3+ ions are accessed by the resonant frequency shifts. Upon cooling, the lifetime of oscillations in the AFM mode increases exponentially and can be subtly tuned by varying the Sm dopant. These results lead to an improved understanding of dopant-tuned spin wave dynamics and magnetoanisotropy parameter in rare-earth orthoferrites.